2021
DOI: 10.1111/jace.17629
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐property relations in crack‐resistant alkaline‐earth aluminoborosilicate glasses studied by solid state NMR

Abstract: The effect of the average ionic potential ξ = Ze/r of the network modifier cations on crack initiation resistance (CR) and Young's modulus E has been measured for a series of alkaline‐earth aluminoborosilicate glasses with the compositions 60SiO2–10Al2O3–10B2O3–(20−x)M(2)O–xM’O (0 ≤ x ≤ 20; M, M’ = Mg, Ca, Sr, Ba, Na). Systematic trends indicating an increase of CR with increasing ionic potential, ξ, have been correlated with structural properties deduced from the NMR interaction parameters in 29Si, 27Al, 23Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…26 Nevertheless, elucidating the coordination environment of magnesium and differences in bonding becomes more difficult for glasses containing other modifiers such as sodium cations as well as other network formers such as boron. 27 In the present work, the dissolution data in Figure 4 point to Mg 2+ cations acting most likely as network modifiers in the multicomponent ISG-2 with fairly complex composition (Table 1). In addition, ISG-2 being more prone to dissolution is also consistent with the Raman deconvolution results (vide supra) indicating a lower Q 3 /Q 2 ratio implying a weaker network F I G U R E 5 Dilatometric profiles obtained for the various international simple glass (ISG) samples.…”
Section: Dissolution Behaviorsupporting
confidence: 50%
“…26 Nevertheless, elucidating the coordination environment of magnesium and differences in bonding becomes more difficult for glasses containing other modifiers such as sodium cations as well as other network formers such as boron. 27 In the present work, the dissolution data in Figure 4 point to Mg 2+ cations acting most likely as network modifiers in the multicomponent ISG-2 with fairly complex composition (Table 1). In addition, ISG-2 being more prone to dissolution is also consistent with the Raman deconvolution results (vide supra) indicating a lower Q 3 /Q 2 ratio implying a weaker network F I G U R E 5 Dilatometric profiles obtained for the various international simple glass (ISG) samples.…”
Section: Dissolution Behaviorsupporting
confidence: 50%
“…Another 9% decrease in the B[IV] proportion was observed when 7.5% of the calcium was substituted by magnesium in the same proportion (N19M8). This has also been seen in different compositions by Backhouse et al 14 or Logrado et al 12 Quintas et al 100,101 noticed that the cation MFS (see Equation ) affects its ability to charge‐compensate for boron atoms. A higher MFS induces a decrease in the charge‐compensating abilities 56,58,79,102 …”
Section: Discussionmentioning
confidence: 61%
“…Some studies suggest that magnesium can be found in both tetrahedral and octahedral forms in glasses, even if the calculation gives a mean coordination number value of approximately 5 20,46 . The presence of tetrahedral magnesium indicates that it could behave similar to an intermediate cation: between a network former and modifier 12,15,21,24,107 . Watts et al 21 suggested that this behavior is more often seen in a highly disrupted glass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The understanding of CR is of high interest. There are many studies trying to elucidate the underlying parameters affecting crack resistance [6,22,52,[60][61][62][63][64][65][66][67][68][69][70][71][72]. Their purpose is to advance the understanding of glass science and provide the possibility of modeling CR with the aim of developing more crack-initiation-resistant glasses [3,73,74].…”
Section: Crack Resistancementioning
confidence: 99%